Experimental assessment of proton dose calculation accuracy in inhomogeneous media. (June 2017) - Sorriaux, J.; Testa, M.; Paganetti, H.; Orban de Xivry, J.; Lee, J.A.; Traneus, E.; Souris, K.; Vynckier, S.; Sterpin, E.
Highlights: An experiment to maximize the effect of heterogeneities in proton beam is proposed. Monte Carlo dose engines performed overall satisfactorily. Large deviations are observed with pencil beam algorithm. Abstract: Purpose: Proton therapy with Pencil Beam Scanning (PBS) has the potential to improve radiotherapy treatments. Unfortunately, its promises are jeopardized by the sensitivity of the dose distributions to uncertainties, including dose calculation accuracy in inhomogeneous media. Monte Carlo dose engines (MC) are expected to handle heterogeneities better than analytical algorithms like the pencil-beam convolution algorithm (PBA). In this study, an experimental phantom has been devised to maximize the effect of heterogeneities and to quantify the capability of several dose engines (MC and PBA) to handle these. Methods: An inhomogeneous phantom made of water surrounding a long insert of bone tissue substitute (1 × 10 × 10 cm 3 ) was irradiated with a mono-energetic PBS field (10 × 10 cm 2 ). A 2D ion chamber array (MatriXX, IBA Dosimetry GmbH) lied right behind the bone. The beam energy was such that the expected range of the protons exceeded the detector position in water and did not attain it in bone. The measurement was compared to the following engines: Geant4.9.5, PENH, MCsquare, as well as the MC and PBA algorithms of RayStation (RaySearch Laboratories AB). Results: For a γ-index criteria of 2%/2 mm, the passing rates are 93.8% for Geant4.9.5, 97.4% for PENH, 93.4% for MCsquare, 95.9% for RayStation MC, and 44.7% for PBA. The differences in γ-index passing rates between MC and RayStation PBA calculations can exceed 50%. Conclusion: The performance of dose calculation algorithms in highly inhomogeneous media was evaluated in a dedicated experiment. MC dose engines performed overall satisfactorily while large deviations were observed with PBA as expected.